Field study of the improved rapid sand fly exposure test in areas endemic for canine leishmaniasis - Willen, Laura; Lestinova, Tereza; Kalousková, Barbora; Sumova, Petra; Spitzova, Tatiana; Velez, Rita; Domenech, Ester; Vaněk, Ondřej; Gállego, Montserrat; Mertens, Pascal; Volf, Petr (PLoS neglected tropical diseases, 2019)
BACKGROUND: Canine leishmaniasis (CanL) is a severe chronic disease caused by Leishmania infantum and transmitted by sand flies of which the main vector in the Western part of the Mediterranean basin is Phlebotomus perniciosus. Previously, an immunochromatographic test (ICT) was proposed to allow rapid evaluation of dog exposure to P. perniciosus. In the present study, we optimized the prototype and evaluated the detection accuracy of the ICT in field conditions. Possible cross-reactions with other hematophagous arthropods were also assessed. METHODOLOGY/PRINCIPAL FINDINGS: The ICT was optimized by expressing the rSP03B protein in a HEK293 cell line, which delivered an increased specificity (94.92%). The ICT showed an excellent reproducibility and inter-person reliability, and was optimized for use with whole canine blood which rendered an excellent degree of agreement with the use of serum. Field detectability of the ICT was assessed by screening 186 dogs from different CanL endemic areas with both the SGH-ELISA and the ICT, and 154 longitudinally sampled dogs only with the ICT. The ICT results corresponded to the SGH-ELISA for most areas, depending on the statistical measure used. Furthermore, the ICT was able to show a clear seasonal fluctuation in the proportion of bitten dogs. Finally, we excluded cross-reactions between non-vector species and confirmed favorable cross-reactions with other L. infantum vectors belonging to the subgenus Larroussius. CONCLUSIONS/SIGNIFICANCE: We have successfully optimized the ICT, now also suitable to be used with whole canine blood. The test is able to reflect the seasonal fluctuation in dog exposure and showed a good detectability in a field population of naturally exposed dogs, particularly in areas with a high seroprevalence of bitten dogs. Furthermore, our study showed the existence of favorable cross-reactions with other sand fly vectors thereby expanding its use in the field.
Keywords: Dogs; Mice, Inbred BALB C; Immunoassay; nemoci psů; imunoanalýza; Insect Vectors; psi; Leishmaniasis; myši inbrední BALB C; leishmanióza; Animals; Female; ženské pohlaví; Phlebotomus; hmyz - vektory; zvířata; Dog Diseases; Leishmania infantum